Selection effects with heterogeneous firms - Neary, P; Mrazova, M (University of Oxford, 2011)
We provide a general characterization of which firms will select alternative ways of serving a market. If and only if firms' maximum profits are supermodular in production and market-access costs, more efficient firms will select into the activity with lower market-access costs. Our result applies in a range of models and under a variety of assumptions about market structure. We show that supermodularity holds in many cases but not in all. Exceptions include FDI (both horizontal and vertical) when demands are "sub-convex" (i.e., less convex than CES), fixed costs that vary with access mode, and R&D with threshold effects.